2018
DOI: 10.1109/tla.2018.8327409
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Assessment of a Large Electrical Grid by New Graph Theory Approach

Abstract: In previous research a novel methodology to assess structural vulnerability was proposed and applied in IEEE test system and high voltage transmission networks of 94 buses, by using graph theory to investigate various risk scenarios that can trigger cascading failures. In this paper, we ratify the application of this methodology in larger networks by applying a case study on the transmission network 230 and 400 kV of Mexico. The events of cascading failures are simulated through two elimination strategies: by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 19 publications
0
37
0
2
Order By: Relevance
“…A low‐efficiency value indicates that the flow travels between many nodes efalse¯=1N)(N1ij1di,j The geodesic vulnerability )(vfalse¯ is an index that measures the performance of the network against contingencies, and it normalises (4) in relation to its base case [40]. This index ranges between zero and one; the greater the index is, the greater its impact on the network vfalse¯=1ij)(1/di,jLCij)(1/di,jBC This index has proved to be useful for quantifying the load that is disconnected due to disintegration processes caused by cascading failures [11, 12, 37]. The geodesic vulnerability index is also used in this study to evaluate the structural robustness of the coupled electricity and natural gas network.…”
Section: Methodology For Assessing the Structural Robustness Of Couplmentioning
confidence: 99%
See 1 more Smart Citation
“…A low‐efficiency value indicates that the flow travels between many nodes efalse¯=1N)(N1ij1di,j The geodesic vulnerability )(vfalse¯ is an index that measures the performance of the network against contingencies, and it normalises (4) in relation to its base case [40]. This index ranges between zero and one; the greater the index is, the greater its impact on the network vfalse¯=1ij)(1/di,jLCij)(1/di,jBC This index has proved to be useful for quantifying the load that is disconnected due to disintegration processes caused by cascading failures [11, 12, 37]. The geodesic vulnerability index is also used in this study to evaluate the structural robustness of the coupled electricity and natural gas network.…”
Section: Methodology For Assessing the Structural Robustness Of Couplmentioning
confidence: 99%
“…In addition, several authors, such as [11, 12], have created methodologies that used the geodesic vulnerability index to evaluate the structural vulnerability of the electrical networks of Mexico, Spain, and Colombia. These studies analysed the expansion plans for the networks and concluded that the investments made do not improve their vulnerability to deliberate attacks.…”
Section: Introductionmentioning
confidence: 99%
“…We use the geodesic vulnerability index ( ν) and impact on connectivity (S) to measure the functionality of the combined electric power and gas network, with respect to the stable condition, when the functionality of a node is compromised. These indexes have been applied to both IEEE test networks and actual electrical networks [26,27]. Although the potential of these indexes has been shown in electrical networks, they have not been applied in coupled networks, which is the goal of this work.…”
Section: Measures Of Vulnerability In Networkmentioning
confidence: 99%
“…To determine the impact of cascading failure events, power grid performance is measured according to the electrical loads that remain connected after several interdiction events. Some measures have been applied to previous research works to estimate load shedding as a percentage of the total system demand [12][13][14] article, we propose the unsatisfied demand (UD) index to measure the power system performance when it is subject to cascading failures caused by disconnection of overloaded power lines. The UD metric allows determining the impact of cascading failures by quantifying the demand that can be satisfied in the electrical infrastructure after multiple line removals.…”
Section: Structural Vulnerability Assessmentmentioning
confidence: 99%